INTERDEPENDENSI ANTARA KEBIJAKAN DIVIDEND PAYOUT RATIO, FINANCIAL LEVERAGE, DAN INVESTASI (Students' Journal of Accounting and Banking, 2013)
The purposes of this study is to analyzed the interdependence of dividend payout ratio, financial leverage, and invesment. Pecking order theory is the basic theory used to explane of that interdependence. The population in this study were manufacturing companies listed in Indonesia Stock Exchange from 2008-2011. The data source of this study were financial statemens of manufacturing companies listed in Indonesia Stock Exchange from 2008-2011. The data collected was analyzed using Two Stage Least Square. The result of this study found that investment has negative significant’s influence to dividend payout ratio but the dividend payout ratio has negative insignificant’s influence investment, it means the dividend payout ratio and the investment do not have a relationship of interdependence. Divident payout ratio has positive insignificant’s influence to financial leverage but the financial leverage has negative insignificant’s to divident ratio, therefor Divident payout ratio variable and financial leverage do not have interdependence relationship. Financial leverage has positive insignificant’s influence to investment and investment has positive insignificant’s to financial leverage, means financial leverage have a relationship of interdependence of investments.Keywords: pecking order theory, dividend payout ratio, financial leverage, investment